Egy extenzív gyepterület félintenzifikációja növény- és talajkondicionálással - Kovács, Györgyi; Pál, Vivien; Tuba, Géza; Csizi, István; Zsembeli, József (Gyepgazdálkodási Közlemények, 2021)
In the last century, the area of European grasslands was declining, as a significant part of them were turned to built-up areas, broken or afforested. In addition to the area reduction, in a significant part of Central, Northern and Western Europe, cultivation has been intensified in the cases of former natural and semi-natural, mostly extensively cultivated grasslands in order to produce higher biomass. Pesticides, organic and mineral fertilizers are also used on the lawns, the frequency of mowing increased and the lawns were reseeded. The structural of grasslands also changed significantly.